Basic hydrographic information about the rivers and temporary watercourses of the Balkash-Alakol basin - Alimkulov, С.К.; Myrzakhmetov, A.B.; Tursunova, А.А.; Isakan, G.; Dostayeva, A.Zh.; Kanay, M.A. (Fundamental and Experimental Biology, 2023)
The article presents basic information about the state of the river network in the Balkash-Alakol basin. They consist of a list of rivers and temporary watercourses from 5 km in mountainous areas and from 10 km in lowland areas, and also include information on their main morphological and morphometric characteristics, which were presented only in the 1970s, after the 1970s such extensive research has not been done. The purpose of the study is to identify rivers and temporary streams, as well as to obtain basic hydrographic information through field surveys and with the help of modern GIS technologies. To achieve the goals, complex field work was carried out using modern hydrological and geodetic equipment and interpretation of space images of Sentinel 1,2 satellites using ArcGIS tools and programs. Each river and temporary watercourse record has a unique feature identifier in the geographic information system. The database is intended for use in regional studies in the field of hydrology, ecology, nature management, and is also an information source for the implementation of measures to monitor and restore rivers, organize water use in transboundary river basins.